Surface plasmon polariton-induced hot carrier generation for photocatalysis. Issue 9 (9th February 2017) - Ahn, Wonmi; Ratchford, Daniel C.; Pehrsson, Pehr E.; Simpkins, Blake S.
Abstract : SPPs on a metal/TiO2 heterostructure enable plasmon-mediated chemistry in a system whose resonance may be continuously tuned via excitation angle. Abstract : Non-radiative plasmon decay in noble metals generates highly energetic carriers under visible light irradiation, which opens new prospects in the fields of photocatalysis, photovoltaics, and photodetection. While localized surface plasmon-induced hot carrier generation occurs in diverse metal nanostructures, inhomogeneities typical of many metal–semiconductor plasmonic nanostructures hinder predictable control of photocarrier generation and therefore reproducible carrier-mediated photochemistry. Here, we generate traveling surface plasmon polaritons (SPPs) at the interface between a noble metal/titanium dioxide (TiO2 ) heterostructure film and aqueous solution, enabling simultaneous optical and electrochemical interrogation of plasmon-mediated chemistry in a system whose resonance may be continuously tuned via the incident optical excitation angle. To the best of our knowledge, this is the first experimental demonstration of SPP-induced hot carrier generation for photocatalysis. We found electrochemical photovoltage and photocurrent responses as SPP-induced hot carriers drive both solution-based oxidation of methanol and the anodic half-reaction of photoelectrochemical water-splitting in sodium hydroxide solution. A strong excitation angle dependence and linear power dependence in the electrochemical photocurrent confirm that the photoelectrochemical reactions are SPP-driven. SPP-generated hot carrier chemistry was recorded on gold and silver and with two different excitation wavelengths, demonstrating potential for mapping resonant charge transfer processes with this technique. These results will provide the design criteria for a metal–semiconductor hybrid system with enhanced hot carrier generation and transport, which is important for the understanding and application of plasmon-induced photocatalysis.